2019
DOI: 10.3390/mps2020042
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time In Vitro Fluorescence Anisotropy of the Cyanobacterial Circadian Clock

Abstract: Uniquely, the circadian clock of cyanobacteria can be reconstructed outside the complex milieu of live cells, greatly simplifying the investigation of a functioning biological chronometer. The core oscillator component is composed of only three proteins, KaiA, KaiB, and KaiC, and together with ATP they undergo waves of assembly and disassembly that drive phosphorylation rhythms in KaiC. Typically, the time points of these reactions are analyzed ex post facto by denaturing polyacrylamide gel electrophoresis, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Such a scenario might allow the [KaiA]/[KaiC] ratio to be an important parameter in vivo for adjusting the sensitivity of the clock to the daily metabolic rhythm of the cell. To address this question, we characterized the dependence of the period of the in vitro KaiABC oscillator on [KaiA] and %ATP using a fluorescence polarization assay (Leypunskiy et al , ; Heisler et al , ) (Figs D and EV3A and B). Consistent with the hypothesis, we found that low KaiA concentration enhances the period sensitivity to %ATP compared to the standard condition (1.5 μM KaiA).…”
Section: Resultsmentioning
confidence: 99%
“…Such a scenario might allow the [KaiA]/[KaiC] ratio to be an important parameter in vivo for adjusting the sensitivity of the clock to the daily metabolic rhythm of the cell. To address this question, we characterized the dependence of the period of the in vitro KaiABC oscillator on [KaiA] and %ATP using a fluorescence polarization assay (Leypunskiy et al , ; Heisler et al , ) (Figs D and EV3A and B). Consistent with the hypothesis, we found that low KaiA concentration enhances the period sensitivity to %ATP compared to the standard condition (1.5 μM KaiA).…”
Section: Resultsmentioning
confidence: 99%
“…To more accurately measure the scaling of entrained phase with day length in KaiABC oscillator reactions, we turned to a fluorescence polarization probe that enables automated measurement of oscillator state with high temporal resolution ( Figure 2—figure supplement 1 ) ( Chang et al, 2012 ; Heisler et al, 2017 ). We used this assay to determine clock phases in free-running conditions after entraining the Kai proteins with three metabolic cycles, analogous to the design of the in vivo experiments.…”
Section: Resultsmentioning
confidence: 99%
“…However, the discontinuous nature of these assays meant that multiple samples had to be prepared to provide time-domain information. More recently, fluorescence correlation spectroscopy (FCS) and fluorescence polarization/anisotropy (FA) have been employed to study KaiB binding by fluorophore tagging, producing tagged proteins using either cell free synthesis , or site-directed mutagenesis. , Fluorescence assays are an improvement to previous discontinuous methods as the fluorescence signals could be continuously monitored provided the fluorophore tags are not photobleached. However, the myriad of stoichiometries existing in Kai reaction mixtures, tetrameric and monomeric KaiB and (sub)­stoichiometric KaiBC and KaiABC complexes, ,, invalidate models that assume two species with differing molecular weights.…”
mentioning
confidence: 99%